CircFAM120B Blocks the Development of Colorectal Cancer by Activating TGF-Beta Receptor II Expression via Targeting miR-645 - Yu, You; Lei, Xiao (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are implicated in various human cancers, including colorectal cancer (CRC). The objective of this study was to investigate the function and regulatory mechanism of a novel circRNA, circFAM120B, in CRC development. The expression of circFAM120B, miR-645 and TGF-beta receptor II (TGFBR2) mRNA was detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cellular biological functions, including cell proliferation, migration/invasion and glycolysis metabolism, were assessed using CCK-8 assay, colony formation assay, transwell assay and glycolysis stress test, respectively. Glycolysis progression was also monitored by lactate production and glucose consumption. The expression of glycolysis-related markers and TGFBR2 at the protein level was detected by western blot. The interaction between miR-645 and circFAM120B or TGFBR2 was predicted by bioinformatics analysis and verified by pull-down assay, dual-luciferase reporter assay and RIP assay. In vivo animal experiments were performed to further explore the function of circFAM120B. The expression of circFAM120B was decreased in CRC tissues and cells. CircFAM120B overexpression blocked CRC cell proliferation, migration/invasion and glycolysis metabolism. MiR-645 was a target of circFAM120B, and miR-645 restoration reversed the effects of circFAM120B overexpression. In addition, TGFBR2 was a target of miR-645, and miR-645 inhibition-suppressed CRC cell proliferation, migration/invasion and glycolysis were restored by TGFBR2 knockdown. Moreover, circFAM120B activated the expression of TGFBR2 by targeting miR-645. TGFBR2 also blocked tumor growth in vivo by targeting the miR-645/TGFBR2 axis. CircFAM120B inhibited CRC progression partly by mediating the miR-645/TGFBR2 network, which explained the potential mechanism of circFAM120B function in CRC.